Effects of Ag contents in Sn–xAg lead-free solders on microstructure, corrosion behavior and interfacial reaction with Cu substrate - TUNTHAWIROON, Phacharaphon; KANLAYASIRI, Kannachai (My University, 2019)
The effects of Ag on the microstructure and corrosion behavior of pre-soldering Sn–xAg lead-free solders, and on the formation of intermetallic layer of the solders with Cu substrate were investigated. The Ag contents (x) were 0, 3.0, 3.5, 4.0, and 5.0 wt.%. The Ag content played a role in the morphology of Ag3Sn phase in the solders. The microstructure analysis showed that the β-Sn phase was surrounded by eutectic networks in the 3.0Ag and 3.5Ag solders and large plate-like Ag3Sn formed in the 4.0Ag and 5.0Ag solders. Nonetheless, the Ag content slightly impacted the corrosion behavior of the as-cast solders as characterized using potentiodynamic polarization test. After soldering, only a single layer of a Cu6Sn5 intermetallic compound formed at the Sn–xAg/Cu interface. By comparison, the Cu6Sn5 intermetallic layer of the Ag-doped solders was thinner than that of the 0Ag solder. The fine Ag3Sn particles in the eutectic networks precipitating in the 3.0Ag and 3.5Ag solders effectively hindered the growth of Cu6Sn5 grains compared to large plate-like Ag3Sn in the 4.0 and 5.0Ag solders.
Keywords: Ag3Sn intermetallic phase; corrosion behavior; Cu6Sn5 intermetallic layer; microstructure; Sn–Ag lead-free solders; wettability